Ludność żydowska w Błaszkach i jej główne źródła utrzymania do 1864 r. - Król, Marek (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2012)
Błaszki is a small town situated between Sieradz and Kalisz.The beginnings of Błaszki go back to the 15th century, but the real development of the city was in 18th century, when the city became the property of Lipski family. In 18th century the town began to be settled by Jews, who later gradually became to be the dominant national group among the total population. It is worth noting that in 1793–1811 Błaszki stood out in the Kalisz department because of its percentage of the men of religion of Moses. At the same time in Opatówek and Staw, situated near the town, there were no Jews. Jews dealt with craft and trade, which was the main source of supply for the cities around the Błaszki. Jewish population lived mainly in wooden houses, which were situated around the rectangular market. At the beginning the people organized 10 fairs per year, but since the mid-19th century they organized only 6. There were Sunday`s fairs as well, that were the place of cloth, horses, cattle, corn, seeds and eggs trading. Jewish artisans were involved in weaving, tanning, linening and agriculture. Jewish community showed an interest in the functioning the Jewish municipality that existed in the mid-18th century. In the thirties of the 18th century Błaszki had its own synagogue. Twenty years later the shelter for the poor Jews was created. However, both the majority of manufacturing industries and the limited employment opportunities in agriculture caused that a significant part of the Jews lived in extreme poverty. Emerging crises in agriculture and the epidemic affected the increase in mortality among the men of religion of Moses.